Multiphysical Models for Hydrogen Production Using NaOH and Stainless Steel Electrodes in Alkaline Electrolysis Cell - Ivan Newen Aquigeh; Merlin Zacharie Ayissi; Dieudonné Bitondo (Journal of Combustion)
The cell voltage in alkaline water electrolysis cells remains high despite the fact that water electrolysis is a cleaner and simpler method of hydrogen production. A multiphysical model for the cell voltage of a single cell electrolyzer was realized based on a combination of current-voltage models, simulation of electrolyzers in intermittent operation (SIMELINT), existing experimental data, and data from the experiment conducted in the course of this work. The equipment used NaOH as supporting electrolyte and stainless steel as electrodes. Different electrolyte concentrations, interelectrode gaps, and electrolyte types were applied and the cell voltages recorded. Concentrations of 60 wt% NaOH produced lowest range of cell voltage (1.15–2.67 V); an interelectrode gap of 0.5 cm also presented the lowest cell voltage (1.14–2.71 V). The distilled water from air conditioning led to a minimum cell voltage (1.18–2.78 V). The water from a factory presented the highest flow rate (12.48 × 10−1cm3/min). It was found that the cell voltage of the alkaline electrolyzer was reduced considerably by reducing the interelectrode gap to 0.5 cm and using electrolytes that produce less bubbles. A maximum error of 1.5% was found between the mathematical model and experimental model, indicating that the model is reliable.